Cross sections of deuteron-induced reactions on medium-mass nuclei - Lagoyannis, A.; Konstantinopoulos, T.; Yigitoglou, I.; Spyrou, A.; Perdikakis, G.; Zarkadas, Ch.; Kokkoris, M.; Demetriou, P.; Harissopulos, S. (HNPS Advances in Nuclear Physics, 2019)
Cross section measurements of deuteron-induced reactions on Ni and Ge isotopes have been carried out at energies well below the Coulomb barrier. The preliminary results are compared with statistical model calculations